2023
DOI: 10.1038/s41419-023-06019-0
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetylation by HBO1 (KAT7) activates Wnt/β-catenin signaling to promote leukemogenesis in B-cell acute lymphoblastic leukemia

Abstract: B-cell acute lymphoblastic leukemia (B-ALL) is an aggressive hematological disorder with a dismal prognosis. The dysregulation of histone acetylation is of great significance in the pathogenesis and progression of B-ALL. Regarded as a fundamental acetyltransferase gene, the role of HBO1 (lysine acetyltransferase 7/KAT7) in B-ALL has not been investigated. Herein, we found that HBO1 expression was elevated in human B-ALL cells and associated with poor disease-free survival. Strikingly, HBO1 knockdown inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
(83 reference statements)
1
0
0
Order By: Relevance
“…Consistent with these reports, ectopic expression of the UBE3C-LRP5 (v7) splice variant was the most activating, with a higher number of soft agar colonies, compared to other LRP5-UBE3C (v1) and UBE3C-LRP5 (v1, v2) fusion variants, possibly because of the absence of the DKK1 inhibitory domain of LRP5 in the UBE3C-LRP5 (v7) fusion. Immunofluorescence and western blot analysis of nuclear and cytoplasmic cell fractionation revealed a significantly high accumulation of β-catenin in the nuclear fraction of cells upon overexpression of UBE3C-LRP5 fusion, indicating constitutive activation of the Wnt/β-catenin pathway with upregulated target genes, MYC , CCND1 37 39 , LEF1 , and TCF4 40 – 44 as reported in the literature for multiple cancers. We found that overexpression of UBE3C-LRP5 fusion significantly increased the clonogenic, migratory, and invasive potential of head and neck cancer cells by activating the Wnt/β-catenin pathway, whereas transient knockdown of the fusion, but not full-length LRP5 , suppresses these phenotypes.…”
Section: Discussionsupporting
confidence: 57%
“…Consistent with these reports, ectopic expression of the UBE3C-LRP5 (v7) splice variant was the most activating, with a higher number of soft agar colonies, compared to other LRP5-UBE3C (v1) and UBE3C-LRP5 (v1, v2) fusion variants, possibly because of the absence of the DKK1 inhibitory domain of LRP5 in the UBE3C-LRP5 (v7) fusion. Immunofluorescence and western blot analysis of nuclear and cytoplasmic cell fractionation revealed a significantly high accumulation of β-catenin in the nuclear fraction of cells upon overexpression of UBE3C-LRP5 fusion, indicating constitutive activation of the Wnt/β-catenin pathway with upregulated target genes, MYC , CCND1 37 39 , LEF1 , and TCF4 40 – 44 as reported in the literature for multiple cancers. We found that overexpression of UBE3C-LRP5 fusion significantly increased the clonogenic, migratory, and invasive potential of head and neck cancer cells by activating the Wnt/β-catenin pathway, whereas transient knockdown of the fusion, but not full-length LRP5 , suppresses these phenotypes.…”
Section: Discussionsupporting
confidence: 57%